Consideration of Surrogate Endpoints for Overall Survival Associated With First-Line Immunotherapy in Extensive-Stage Small Cell Lung Cancer - Zhang, Shuang; Li, Shuang; Cui, Yanan; Zhao, Peiyan; Sun, Xiaodan; Cheng, Ying (Frontiers in Oncology, 2021)
Background: The combination of immune checkpoint inhibitors (ICIs) and chemotherapy is known to improve overall survival (OS) in patients with extensive-stage small cell lung cancer (ES-SCLC). ICIs have different response patterns and survival kinetics characteristics from those of the traditional chemotherapy. In first-line treatment for ES-SCLC, there is an urgent need for surrogate endpoints for the early and accurate prediction of OS. This study aimed to assess progression-free survival (PFS), milestone OS rate, milestone restricted mean survival time (RMST), overall response rate (ORR), and disease control rate (DCR) as proposed surrogate endpoints for OS in ES-SCLC for first-line immunotherapy trials. Methods: Between January 1, 2013, and December 2020, published articles on randomized clinical trials of ICIs plus chemotherapy in patients with ES-SCLC as first-line therapy were searched in PubMed. Abstracts from the ESMO, ASCO, and WCLC, reported from 2018 onwards, were also searched. A weighted regression analysis based on the weighted least squares method was performed on log-transformed estimates of treatment effect, and the determination coefficient (R2) was calculated to evaluate the association between treatment effect on the surrogate endpoint and OS. RESULTS: Seven trials, representing 3009 patients, were included to make up a total of 16 analyzed arms. The ratio of the 12-month OS milestone rate (r = -0.790, P = 0.011, R2 = 0.717) and 12-month OS milestone RMST (r = 0.798, P = 0.010, R2 = 0.702) was strongly correlated with the hazard ratio (HR) for OS. The strongest association was observed between the ratio of the 24-month OS milestone RMST and the HR for OS (r = 0.922, P = 0.001, R2 = 0.825). No associations were observed between the HR for OS and PFS and the RR for ORR and DCR. Conclusions: The results suggested a strong correlation among the ratios of OS milestone rates at 12 months, ratios of OS milestone RMSTs at 12 and 24 months, and HR for OS. This indicates that OS milestone rates and OS milestone RMSTs could be considered surrogate endpoints of OS in future first-line immunotherapy trials for ES-SCLC.